Equity valuation of Amorim Group - Martins, João Diogo Ponciano (2019)
The present project intents to perform a valuation of Corticeira Amorim SGPS, S.A. – a Portuguese company that is a part of the Amorim Group, one of the most successful Portuguese origin groups in recent years and the worldwide market leader in the cork sector. The journey of the Amorim Group represents one of the most successful stories in the Portuguese market through the 20th and 21st centuries, marked by a constant search for success, sustainability and innovation. This project will be supported by several different approaches and theoretical models and, ultimately, will provide a target price of the company’s shares as of 31st December 2018. Hence, the primary goal of this project is to deliver potential investors with tools to understand if Corticeira Amorim’s shares are being priced above or below its true intrinsic value. After the valuation process was concluded, a target price of €10.41 was obtained, leading to a recommendation to acquire the shares of Corticeira Amorim.